PENGARUH PENYAJIAN LAPORAN KEUANGAN DAN AKSESIBILITAS LAPORAN KEUANGAN TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH (Studi Pada SKPD Kabupaten Bengkalis) - Nurlaili '; Nur Azlina; Mudrika Alamsyah Hasan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims to (1) examine the effect of the financial statement presentation of the financial management accountability and (2) examine the effect of the accessibility of the financial statements to the accountability of financial management. The method used in this research is total sampling method. Data of this study uses primary data, directly through a questionnaire and analyzed using SPSS version 20. The data were analyzed to test the hypothesis using multiple regression analysis approach. The results showed that the effect on the financial statement presentation of financial management accountability and accessibility affect the accountability of financial management. The test results which found significant results due to the better presentation of the financial statements and the accessibility of the financial statements will be good also government against users of financial statements.Keywords: financial statements, accessibility, accountability, and financial management